LOYALITAS PELANGGAN INTERNET DENGAN MEDIA AKSES TELEPON SELULER - Dadan Sumantri (KarismaPro, 2022)
This research analyses internet customer loyalty with cellular phone access media on internet customers in Bandung. This study used customer satisfaction, service quality, and switching costs to measure internet customer loyalty. The number of samples in this research is as many as 200 respondents, and the sampling technique used is judgment sampling. The results of this study are customer satisfaction variables and switching cost variables that significantly affect the loyalty variable. While the service quality variable significantly affects customer satisfaction but does not significantly affect customer loyalty. Keywords: customer satisfaction, service quality, switching cost, internet provider, mobile cellular